(untitled) (Malaysian Management Journal, 2001)
This study examined the level of transparency among unit trust funds in Malaysia. Unit trust funds were the focus of this study due to its nature: unique, heavily regulated and rapidly growing. The study investigated the extent of disclosure in relation to the various mandatory and voluntary requirements and the roles of the specific characteristics of trust funds in explaining their level of disclosure in the annual reports. The findings showed that the level of disclosure increased rapidly within the period of study suggesting that trust funds were becoming more transparent. With regard to the funds’ specific characteristics, the study showed that the influence was not consistent. The model best explained the disclosure level during the pre-mandatory period, i.e. 1996. During this year, the variables ’sponsor of the fund’ and ’auditors’ significantly influenced the disclosure level in the predicted direction. In the other years (1997 and 1998), the explanatory power of the model was very low as suggested by the significant reduction in the adjusted R2. One argument was that during this period, the revised Guidelines had been issued and thus the model could not explain much the variation in the disclosure level as a large amount of the items in the study were already mandated.